"Barcoding" and ISSR data illuminate a problematic infraspecific taxonomy for Chrysanthemoides monilifera (Calenduleae; Asteraceae): Lessons for biocontrol of a noxious weed. (August 2015) - Barker, Nigel P.; Paterson, Iain; Howis, Seranne
Abstract: Chrysanthemoides monilifera Tourn. ex Medik is a noxious weed in Australia and New Zealand. It is a widespread species in southern Africa, where it shows considerable morphological variation that has resulted in a confusing infraspecific taxonomy. We use DNA sequence data from the nuclear Internal Transcribed Spacer (ITS) region from 78 samples of this species from its indigenous distribution range and 10 samples from Australia and New Zealand to determine the regions of origin of the invasive plants. These data are augmented by a smaller study using ISSR markers. Bayesian Inference analysis was somewhat resolved, with many weakly supported nodes. Clades with support tended to correspond to infraspecific taxonomic entities, and were geographically coherent. In contrast, a neighbour-net analysis was not as well resolved and indicated considerable reticulation. All analyses of ITS data retrieved two major clades corresponding to Western and Eastern distributions, with some overlap. Samples from New Zealand and Australia correspond to the taxon C. monilifera subsp. monilifera, and are resolved as most closely related to samples from the greater Cape Town area. Biological control agent populations for C. monilifera subsp. monilifera should be sourced from this region in order to avoid host plant incompatibility problems. Graphical abstract: Highlights: Chysanthemoides monilifera (Asteraceae) has a complex infraspecific taxonomy. It is also an invasive species in Australia and New Zealand. Internal Transcribed Spacer sequence data partially supported the proposed infraspecific taxonomy. ISSR data from a subset of samples supported the ITS data. Both data sets showed the invasive plants from New Zealand to be closest to plants from the Western Cape of South Africa.